Tradução e adaptação cultural de escalas de ansiedade relacionadas à COVID-19 para o contexto brasileiro - Ferreira, Layana Giselly Silva (2022)
Coronavirus Diseases 2019 (COVID-19) is an infectious disease caused by the new coronavirus (SARS-Cov-2) and has as main symptoms fever, tiredness and dry cough. With high transmissibility, dizzying increase in the number of cases and clinical severity, it is impossible to disregard its psychological effects, such as anxiety. In this context, the use of instruments that measure anxiety related to COVID-19 is relevant, in a reliable and valid way. Chandu et al. (2020) constructed the COVID-19 Anxiety Scale (CAS) in India and Riad et al. (2020) developed the COVID-19 Induced Anxiety Scale (CIAS) in the Czech Republic, both to measure COVID-19-related anxiety. The translation and cultural adaptation of CAS and CIAS for use in Brazil is important, since it will contribute to the future instrumentalization of health professionals in clinical practice and research. The objective of this study was to carry out the translation and cultural adaptation of CAS and CIAS to Brazil. This is a cross-sectional and methodological study, which followed the initial translation stages, translation synthesis, back translation, review by an expert committee and pre-test. All ethical precepts will be respected. The initial translation stage of CAS and CIAS, from English to Brazilian Portuguese, was performed by two independent translators. Then, the consensual version of the scales was established, which were translated back into the original language by a third translator. Subsequently, the revision of the versions of the CAS and CIAS was carried out by a committee composed of eight experts, who carefully analyzed all items of the scales, adapting two items of the CAS and three items of the CIAS, obtained the pre-final version of the scales that in Brazilian Portuguese received the name of Anxiety Scale of COVID-19 and Anxiety Scale Induced by COVID-19. Then, the pre-test was carried out with 47 people, the majority being female (63.8%), of mixed ethnicity (48.9%), single (55.3%), Catholic (42.4%), with mean age and schooling of 33.53 years and 10.76 years, respectively. The percentage of anxious participants related to COVID-19 was (51.1%) and (40.4%), according to the COVID-19 Anxiety Scale and the COVID-19 Induced Anxiety Scale, respectively. The respondents considered the scales clear and understandable. Therefore, it is concluded that the Brazilian version of the CAS and the CIAS is translated and culturally adapted to the Brazilian context. It is expected to develop in the future the analysis of the psychometric properties of the scales, in order to make them available for use in Brazil.